Clostridioides difficile Toxin A-Induced Wnt/β-Catenin Pathway Inhibition Is Mediated by Rac1 Glucosylation - Martins, Conceição S.; Costa, Deiziane V. S.; Lima, Bruno B.; Leitäo, Renata F. C.; Freire, Gildênio E.; Silva, Guilherme F. M.; Pacífico, Dvison M.; Abreu, José G.; Brito, Gerly A. C. (Frontiers in Microbiology, 2020)
Clostridioides difficile toxin A (TcdA) has been shown to inhibit cellular Wnt signaling, the major driving force behind the proliferation of epithelial cells in colonic crypts, likely through the inhibition of β-catenin nuclear translocation. Herein, we aimed to advance the understanding of this mechanism by replicating the findings in vivo and by investigating the specific role of Rac1, a member of the Rho GTPase family, on the inhibition of the Wnt-induced β-catenin nuclear translocation triggered by TcdA. To investigate the effects of TcdA on the Wnt/β-catenin pathway in vivo, we injected the ileal loops of C57BL/6 mice with TcdA (PBS as the control) to induce C. difficile disease-like ileitis. Four hours postinjection, we obtained ileum tissue samples to assess Wnt signaling activation and cell proliferation through Western blotting, immunohistochemistry and qPCR. To assess the role of Rac1 on Wnt signaling inhibition by TcdA, we transfected rat intestinal epithelial cells (IEC-6) with either a constitutively active Rac1 plasmid (pcDNA3-EGFP-Rac1-Q61L) or an empty vector, which served as the control. We incubated these cells with Wnt3a-conditioned medium to induce Wnt/β-catenin pathway activation and then challenged the cells with TcdA. We assessed Wnt signaling activation in vitro with TOP/FOPflash luciferase assays, determined nuclear β-catenin translocation by immunofluorescence, measured cyclin D1 protein expression by Western blotting and quantified cell proliferation by Ki67 immunostaining. In vivo, TcdA decreased β-catenin, cyclin D1 and cMYC expression and inhibited the translocation of β-catenin into the nucleus in the ileum epithelial cells. In addition, TcdA suppressed cell proliferation and increased Wnt3a expression, but did not alter Rac1 gene expression in the ileum tissue. In vitro, constitutively active Rac1 prevented Wnt signaling inhibition by enabling the β-catenin nuclear translocation that had been blocked by TcdA. Our results show that TcdA inhibits Wnt/β-catenin pathway in vivo and demonstrate that this inhibition is likely caused by a Rac1-mediated mechanism.